Ractopamine hydrochloride improves growth performance and carcass composition in immunocastrated boars, intact boars, and gilts - Rikard-Bell, C; Curtis, M.A; van Barneveld, R.J; Mullan, B.P; Edwards, A.C; Gannon, N.J; Henman, D.J; Hughes, P.E; Dunshea, F.R (Journal of animal science, 2009)
The β-agonist ractopamine is a dietary ingredient that improves growth and increases the lean mass with little change in fat mass in gilts and barrows. Limited data in boars indicate that dietary ractopamine may increase lean tissue and decrease fat deposition, whereas there are no data for immunocastrated boars. The aims of this investigation were 1) to assess whether the growth performance of all sexes could be maintained over 31 d by using a step-up dietary ractopamine feeding program of 5 mg/kg of ractopamine for the first 14 d, then increasing the dose to 10 mg/kg for a further 17 d, and 2) to determine if dietary ractopamine would increase lean mass in all sexes and decrease fat mass in boars and immunocastrated boars. The study involved 286 pigs randomized and proportionally allocated by breed into 24 groups of 11 or 12 pigs at 17 wk of age, with equal groups of boars, immunocastrated boars, and gilts. Dietary ractopamine decreased (P = 0.005) ADFI during the first 2 wk, particularly in the intact and immunocastrated boars, with the reduction in ADFI being maintained in the immunocastrated boars after the increment in dietary ractopamine. Daily BW gain was not altered by dietary ractopamine during the first 2 wk, but was increased (P < 0.001) after the increment in dietary ractopamine. Dietary ractopamine decreased (P [less-than or equal to] 0.033) feed conversion ratio in all sexes with the response being greater after the increase in dietary ractopamine. Carcass weight was increased (P < 0.001) by dietary ractopamine in all sexes, whereas back fat tended (P = 0.076) to be reduced in the immunocastrated boars. Dietary ractopamine increased (P = 0.018) lean tissue mass by 4.0, 4.8, and 6.5 kg in the intact boars, gilts, and immunocastrated boars, respectively. In the entire and immunocastrated boars, the increase in lean tissue was accompanied with a decrease (P = 0.004) in fat mass. There was little effect of dietary ractopamine on fat mass in gilts. However, carcass percent fat was decreased (P = 0.004) and percent lean increased (P = 0.006) in all sexes. Immunocastration caused a decrease in lean tissue mass and an increase in fat mass and an increase in ADFI in the last one-half of the study. Dietary ractopamine may decrease fat mass in intact and immunocastrated boars and offers an excellent means of maximizing the effects of immunocastration and minimizing the increase in fat mass sometimes observed in immunocastrated boars.